2015
DOI: 10.1039/c4cp05565a
|View full text |Cite
|
Sign up to set email alerts
|

Improved charge separation via Fe-doping of copper tungstate photoanodes

Abstract: Photoelectrochemical (PEC) water splitting offers a clean pathway to renewable and sustainable energy in the near future. The key to improving the efficiency of PEC devices is the ability to find materials with suitable optoelectronic properties, and identifying, then overcoming their limitations. In this paper, we explore the photoelectrochemical performance of CuWO4 photoanodes for solar water splitting, and find that charge separation is the dominant limitation for this material. As a result, we attempt to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 27 publications
4
51
0
Order By: Relevance
“…Bartlett's group reported that the MnPO-based CuWO 4 photoelectrode exhibited improved PEC performance, corresponding to the cathodic shift of the onset potential for water oxidation by ~ 100 mV and a mild increase in photocurrent density, particularly at low applied bias [11]. In addition, iron doping or hydrogen treatment of the CuWO 4 film increased the bulk electronic conductivity [12]. Another strategy involved formation of heterojunctions between CuWO 4 and a second semiconductor, such as WO 3 , BiVO 4 , and Ag 2 NCN with synergetic enhancement in photocurrent density.…”
Section: Introductionmentioning
confidence: 99%
“…Bartlett's group reported that the MnPO-based CuWO 4 photoelectrode exhibited improved PEC performance, corresponding to the cathodic shift of the onset potential for water oxidation by ~ 100 mV and a mild increase in photocurrent density, particularly at low applied bias [11]. In addition, iron doping or hydrogen treatment of the CuWO 4 film increased the bulk electronic conductivity [12]. Another strategy involved formation of heterojunctions between CuWO 4 and a second semiconductor, such as WO 3 , BiVO 4 , and Ag 2 NCN with synergetic enhancement in photocurrent density.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the scientific studies on the electronic properties of pure and doped CuWO 4 have been mainly focused on the photocatalytic (PC) degradation of organic dyes (Rhodamine B, eosin yellow dye and methylene blue) under ultraviolet and visible light [53][54][55], magnetic [56][57][58][59], photoelectrochemical water splitting [60][61][62][63][64], visible and solar-assisted water splitting [65,66], photoanode for solar water oxidation [67,68], electrical transport [69], and photoluminescence (PL) [24,53,70]. An important point to be considered is that the theoretical studies [16,[71][72][73][74][75], performed by means of ab initio calculations based on the density-functional theory (DFT) for the electronic structure of CuWO 4 crystals, have shown that the conduction band (CB) of this oxide is composed of 3d orbitals (Cu atoms) and 5d orbitals (W atoms), while the valence band (VB) is formed of 2p orbitals (O atoms).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to WO 3 that is only stable in acidic solutions, CuWO 4 shows an excellent stability in aqueous solutions with a pH range of 7-9 [161][162][163]. However, the obtained PEC performances of the CuWO 4 photoanodes are still far from their theoretical values considering the bandgap of 2.3 eV, and the major limitation is attributed to the low charge carrier mobility (~ 0.006 cm 2 V −1 s −1 ) and short charge diffusion length (~ 30 nm) that cause poor charge separation in the bulk CuWO 4 [164,165]. In addition, the surface states also affect the PEC water oxidation performance of the CuWO 4 photoanodes [166,167].…”
Section: Tungsten-based Ternary Oxidesmentioning
confidence: 98%